ダイ20ジ ナンキョク チイキ カンソク タイ キショウ ブモン ホウコク 1979 - 召田, 成美; メシダ, シゲミ; 塚村, 浩二; ツカムラ, コウジ; 山本, 雄次; ヤマモト, ユウジ; 古謝, 三行; コシャ, ミツユキ; Meshida, Shigemi; Tsukamura, Koji; Yamamoto, Yuji; Kosha, Mitsuyuki (1983)
P(論文) この報告は第20次南極地域観測越冬隊気象部門が, 1979年2月1日から1980年1月31日まで, 昭和基地において行った地上および高層気象観測の結果をまとめたものである。観測方法, 設備, 結果の取り扱い等はほぼ19次隊と同じである。越冬期間中特記される気象現象としては, 次のものがあげられる。1) 秋から冬のはじめにかけて, ぐずつき気味の風の強い日が多く, 特に4月の月平均風速は累年平均(1957年-1979年)を3.2m/sも上まわった。2) ブリザードは平年とほぼ同数襲来したが, 長続きするものは少なく, 天気の回復が早かった。3) 6,7月の平均気温が累年平均より2℃以上低く, 年間の変化傾向が「なべ底型」に近かった。4) 成層圏の突然昇温が平年より1ヵ月も早く現れた。5) 9月から12月にかけ長い周期で天気が変化し, 特に9月下旬から10月下旬, 11月下旬から12月下旬にかけては1ヵ月以上好天が持続した。 This paper describes the results of meteorological observations (mainly surface and aerological) at Syowa Station from February 1,1979 to January 31,1980. Methods and equipments for observations are the same as in 1978. The observed data were sent to World Meteorological Center at Melbourne via Mawson Station according to the WMO Regulations. Remarkable characteristics are as follows : 1) The weather remained unsettled with strong wind between autumn and the beginning of winter. Especially in April the monthly mean wind speed was 3.2 m/s higher than the normal. 2) The number of blizzards was almost the same as that of the average. But a few blizzards had lasted long. 3) Annual variation of temperature became pot-shaped, because in June and July the monthly mean temperatures were lower by 2℃ or more. 4) Stratospheric sudden warming had occurred one-month earlier. 5) Fine weather kept on one month or more from September to October and from November to December. departmental bulletin paper